Study on the pharmacological character of an insulin-mimetic small molecular compound of vanadyl trehalose - Umar, M; Qian, W; Liu, Q; Xing, S; Li, X; Yang, X; Fan, Y; Ma, D; Jiang, P; Li, M (Physiological research, 2020)
To investigate the effect of vanadyl trehalose (VT) on oxidative stress and reduced glutathione/glutathione-S-transferase (GSH/GSTs) pathway gene expression in mouse gastrointestinal tract, as well as the protective effects of vitamin C (VC) and reduced glutathione (GSH). Thirty male Kunming mice were randomly divided into five groups: control group (group A), VT group (group B), VC + VT group (group C), GSH + VT group (group D) and VC + GSH + VT group (group E). The content of reduced glutathione (GSH) and glutathione peroxidase (GSH-Px) activity and the expressions of glutamate-cysteine ligase catalytic subunit (GCLC), glutathione synthetase (GSS), regulated through glutathione reductase (GSR) and glutathione-S-transferase pi (GSTpi) in stomach and duodenum in vanadyl trehalose treated group were lower than those in group A (P<0.05). The C, D, E group can significantly improve the above indicators, but those only in the stomach in E group reached the level of the control group. Vanadyl trehalose (VT) was able to cause oxidative stress damage to the gastrointestinal tract of mice, which affects GSH content and GSH-Px activity and interferes with the normal expression of GSH/GSTs pathway. Exogenous vitamin C, reduced glutathione and the combination of the two could play a specific role in antioxidant protection and reduce the toxicity of vanadyl trehalose.
Keywords: Ascorbic Acid; Animals; Trehalose; Antioxidants; Vanadates; glutathion; oxidační stres; glutathionperoxidasa; Glutathione; Oxidative Stress; glutathiontransferasa; Hypoglycemic Agents; Mice; Glutathione Transferase; Insulin; Glutathione Peroxidase; myši; hypoglykemika; biomimetika; žaludek; Male; vanadáty; antioxidancia; kyselina askorbová; zvířata; mužské pohlaví; Glutathione Reductase; trehalosa; glutathionreduktasa; inzulin; Biomimetics; Stomach